Inverted Perovskite Photovoltaics Using Flame Spray Pyrolysis Solution Based CuAlO2/Cu−O Hole-Selective Contact - Savva, Achilleas; Papadas, Ioannis T.; Tsikritzis, Dimitris; Ioakeimidis, Apostolos; Galatopoulos, Fedros; Kapnisis, Konstantinos; Fuhrer, Roland; Hartmeier, Benjamin; Oszajca, Marek F.; Luechinger, Norman A.; Kennou, Stella; Armatas, Gerasimos S.; et al. (My University, 2019)
We present the functionalization process of a conductive and transparent CuAlO2/Cu-O hole-transporting layer (HTL). The CuAlO2/Cu-O powders were developed by flame spray pyrolysis and their stabilized dispersions were treated by sonication and centrifugation methods. We show that when the supernatant part of the treated CuAlO2/Cu-O dispersions is used for the development of CuAlO2/Cu-O HTLs the corresponding inverted perovskite-based solar cells show improved functionality and power conversion efficiency of up to 16.3% with negligible hysteresis effect.
Keywords: CuAlO2/Cu-O alloying; Delafossite oxides; Flame spray pyrolysis; Hole-transporting layers; Perovskites solar cells